A miniaturized reconfigurable unlicensed ultra‐wideband antenna with multiple band‐notch performance. Issue 8 (20th April 2021) - Han, Liping; Chen, Jin; Han, Guorui; Chen, Xinwei; Ma, Runbo; Zhang, Wenmei
Abstract: This paper presents a compact reconfigurable ultra‐wideband antenna with multiple band‐notch characteristic. The truncated corners in the rectangular patch are employed to realize the desired ultra‐wideband (UWB) operation. The band‐notch property in the 3.5 GHz WiMAX and 5.2 GHz WLAN bands are obtained by the conventional C‐shaped slots in the radiating patch, and the band‐notch performance in the 7.5 GHz X‐band is especially realized by introducing a parasitic meandering strip beneath the ground. The reconfigurable band‐notch function is achieved by controlling the states of the PIN diodes inserted in the band‐notch structures. The overall dimension of the antenna is 19.5 mm × 14 mm. The simulation and experiment results confirm that the antenna can switch between a UWB state, three single band‐notch states, three dual band‐notch states and a triple band‐notch state. Moreover, stable radiation patterns are exhibited.